Analysis of Microplastic Abundance in Lake Siombak, Medan Marelan, Medan - Jaka Ramananda; Ternala Alexander Barus; Arif Nuryawan (Tunas Geografi, 2023)
Microplastics are one of the pollutants that threaten aquatic ecosystems and have become the focus of research in recent years by environmentalists worldwide. In addition to harmful base materials, microplastics have hydrophobic characteristics, so chemicals such as Persistent Organic Pollutants can stick to microplastics and cause chemical pollution in aquatics. Siombak Lake is located in the coastal area of Medan City, and it is predicted to be a microplastic distribution channel to the aquatics. This study aimed to analyze the abundance of microplastics in water, sediment, and fish in Siombak Lake. Sampling was conducted from November 2021 â€“ January 2022 at Siombak Lake. Water samples to be analyzed were added with 90 g NaCl, then filtered and separated visually using a microscope. Microplastic in the sediment is separated by drying, volume reduction, density separation, filtration, and visual sorting. Fish samples were dissected, and then the digestive tract content of fish was diluted with 10 ml of saturated NaCl. The abundance of microplastics obtained in waters ranged from 93-519 particles/m3, and the Number of microplastics in sediment ranged from 521-1481 particles/kg dry sediment, while the abundance of microplastics in fish samples ranged from 0-6 particles/individual.Keywords: Microplastic, Abundance, Coastal, Pollutant, Siombak LakeÂ